Cardiovascular magnetic resonance imaging in suspected cardiac tumour: a multicentre outcomes study. (21st September 2021) - Shenoy, Chetan; Grizzard, John D; Shah, Dipan J; Kassi, Mahwash; Reardon, Michael J; Zagurovskaya, Marianna; Kim, Han W; Parker, Michele A; Kim, Raymond J
Abstract: Aims: Cardiovascular magnetic resonance (CMR) imaging is a key diagnostic tool for the evaluation of patients with suspected cardiac tumours. Patient management is guided by the CMR diagnosis, including no further testing if a mass is excluded or if only a pseudomass is found. However, there are no outcomes studies validating this approach. Methods and results: In this multicentre study of patients undergoing clinical CMR for suspected cardiac tumour, CMR diagnoses were assigned as no mass, pseudomass, thrombus, benign tumour, or malignant tumour. A final diagnosis was determined after follow-up using all available data. The primary endpoint was all-cause mortality. Among 903 patients, the CMR diagnosis was no mass in 25%, pseudomass in 16%, thrombus in 16%, benign tumour in 17%, and malignant tumour in 23%. Over a median of 4.9 years, 376 patients died. Compared with the final diagnosis, the CMR diagnosis was accurate in 98.4% of patients. Patients with CMR diagnoses of pseudomass and benign tumour had similar mortality to those with no mass, whereas those with malignant tumour [hazard ratio (HR) 3.31 (2.40–4.57)] and thrombus [HR 1.46 (1.00–2.11)] had greater mortality. The CMR diagnosis provided incremental prognostic value over clinical factors including left ventricular ejection fraction, coronary artery disease, and history of extracardiac malignancy ( P < 0.001). Conclusion: In patients with suspected cardiac tumour, CMR has high diagnostic accuracy. Patients with CMR diagnoses of no mass, pseudomass, and benign tumour have similar long-term mortality. The CMR diagnosis is a powerful independent predictor of mortality incremental to clinical risk factors. Graphical Abstract: